Goodbye California - MacLean, Alistair (Glasgow William Collins Sons & Company Ltd., 1977)
The classic tale of terrorism, where a criminal fanatic is hell-bent on blasting San Francisco into the ocean, from the acclaimed master of action and suspense. 'Earthquake country, 'said the Professor. 'San Francisco is geologically and seismologically a city that waits to die. Los Angeles is ringed by earthquake centres - seven massive quakes so far. We have no idea where the next, the monster, will hit'' 'until a criminal fanatic kidnaps a nuclear scientist and builds his own atomic bombs. If exploded on California's fault lines they could trigger off the mightiest earthquake of them all - killing half its population and dumping the entire city of San Francisco into the sea.
English Fiction.
Keywords: California -- Terrorism -- Detective and mystery stories